Energetic Adaptations of Bivalves Under Environmental Stress: A Comprehensive Review on Bioenergetics and Aquaculture Sustainability - Chunhua Liu; Yueyong Shang; Shanza Gul; Menghong Hu; Youji Wang (Reviews in Aquaculture, 2025)
Bioenergetics, or scope for growth (SFG), is a model used to assess the health and adaptability of mollusks to external factors. It achieves this by converting physiological responses, such as clearance rate (CR), respiration rate (RR), excretion rate (ER), absorption efficiency (AE), and oxygen–nitrogen ratio (O:N ratio), into energy equivalents. This biomarker reflects the energy available for growth and reproduction, indicating an organism's potential to adapt to environmental change and revealing the energetics behind growth. It has been a significant focus in marine ecology, biology, and aquaculture of mollusks. To understand the effects of various factors on the bioenergetics of bivalves, the effects of temperature, ocean acidification (OA), salinity, dissolved oxygen (DO), trace elements (e.g., copper (Cu), zinc (Zn), cadmium (Cd)), micro/nanoparticles (MPs/NPs), harmful algae, and other factors on the physiology and energy budget of bivalves were summarized and analyszed in this paper. We found that some influencing factors (e.g., OA, trace elements, and harmful algae) serve as selective pressures that make bivalves adapt to environmental changes, and the impacts of various stressors on the SFG in bivalves are diverse. However, under hypoxia and salinity changes, exceeding bivalve tolerance can lead to metabolic disorders and reduced SFG, impacting populations and aquaculture. At the same times, we analyzed WOS literature from 1980 to 2023 using VOS‐viewer software to assess how climate change and pollutants affect bivalve energy assimilation and consumption, offering insights for bivalve biology and aquaculture research.